BANK-SPECIFIC FACTORS AND LENDING BEHAVIOUR IN SUB-SAHARAN AFRICA - Ibrahim Bello Abdullahi; Hussain Umar (Malete Journal of Accounting and Finance)
The intermediary function carried out by commercial banks in moving financial resources from surplus units to deficit units continues to be most critical to economic activities across the globe including sub-Saharan Africa. However, literature revealed that challenges involving inadequate capital, poor asset quality and smaller bank sizes constrain the lending capacity of commercial banks in sub-Saharan Africa, leading to inefficient intermediation, weak lending capacity and financial underdevelopment. Therefore, this study aimed at examining the effect of bank-specific factors on lending behaviour in Sub-Saharan Africa. This study employed ex post facto research design. Population of the study consists of fifty-four (54) African nations within the sub-Sahara African region, while 14 sub-Sahara African countries were purposively drawn as the sample size of the study. Secondary data were sourced from World Development Indicators (WDI) and African Financials covering the period of 1990 to 2022. The study employed pooled ordinary least squares (POLS) regression method for the analysis. The results were that: capital adequacy ratio (β = 0.289; p-value = 0.000); asset quality (β = 0.306; p-value = 0.003); and bank size (β = 3.928; p-value = 0.000) have significant positive effect on lending behaviour in the SSA region. The study concluded that bank-specific factors affect lending behaviour in sub-Saharan Africa. The study therefore recommended that management of commercial banks in the SSA region should pursue growth strategies like mergers and acquisitions to achieve economies of scale and improve lending capacity; and policymakers should implement flexible guidelines for capital adequacy tailored to the unique economic conditions of sub-Saharan Africa, so as to ensure financial stability without over-restricting banks' lending capacities.